Firm Performance and Women on the Board: Evidence from Spanish Small and Medium-Sized Enterprises - Martín-Ugedo, Juan Francisco; Minguez-Vera, Antonio (Feminist economics, 2014)
This study examines gender diversity on boards of directors in a sample of nonfinancial Spanish small and medium-sized enterprises (SMEs) for 2003-8, finding that the probability of women on the board increases with firm performance, defined as return on assets, and family ownership, but diminishes with corporate ownership and firm risk. It also finds, when examining the full sample, a positive effect of the presence of women board members on firm performance. The study also obtains a similar positive effect in most subsamples, including in firms with corporate ownership, where family connections play less role in the election of board members, and in firms in the secondary and tertiary sectors, which are characterized by having greater proximity to final consumers than those in the primary sector.